PERANCANGAN SISTEM INFORMASI AKUNTANSI PERSEDIAAN BAHAN BAKU DAGING BERBASIS WEB MENGGUNAKAN LARAVEL DAN HEIDISQL PADA PT. KIRANA SEMESTA PANGAN - WAHYU NURJAYA WK (Jurnal Teknologi Informasi, 2022)
PT. Kirana Semesta Pangan is a company engaged in the industrial sector which produces beef meatballs mixed with chicken. The obstacle faced was the difficulty of controlling the stock of meat raw materials which caused spoiled material to occur, as a result the company suffered losses because the available materials could not be used properly and for the process of reporting to the central leadership it was difficult to control the materials and reports. To facilitate this, all can be realized by designing a website-based raw material inventory accounting information system. This website built aims to help PT. Kirana Semesta Pangan in terms of stock management of meat raw materials. The raw material inventory method is designed to use the FIFO method, where the first goods in are the first outgoing goods. The results achieved are that PT. Kirana Semesta Pangan requires a raw material inventory application system, making it easier to manage company assets and with the creation of this system it is hoped that raw material control can be well organized.